A Combined Microsurgical and Endovascular Approach to Giant Paraclinoid Aneurysm: 2-Dimensional Operative Video. Issue 6 (29th April 2021) - Pojskić, Mirza; Arnautović, Kenan I; Ibn Essayed, Walid; Al-Mefty, Ossama
Abstract: Giant paraclinoid aneurysm remains a treatment challenge because of their complex anatomy and surgical difficulties stems frequently from a calcified or atherosclerotic aneurysmal neck and compression of the optic pathways. 1 - 9 To improve exposure, facilitate the dissection of the aneurysm, assure vascular control, reduce brain retraction and temporary occlusion time, and enable simultaneous treatment of possible associated aneurysms, we combined the cranio-orbital zygomatic (COZ) approach 9 with endovascular balloon occlusion of the internal carotid artery (ICA) and suction decompression of the aneurysm. 4 The patient is a 50-yr-old female who presented with headache and hemianopsia. MRI, CT, and 4-vessel angiography revealed a giant right ophthalmic paraclinoid partially thrombosed aneurysm. Surgery was performed via right COZ approach with removal of the anterior clinoid. Unroofing the optic canal and opening the falciform ligament and the optic sheath, allowing the dissection and mobilization of the optic nerve from the aneurysm and the origin of ophthalmic artery. The endovascular team placed a deflated, double lumen balloon catheter in the ICA 2 cm above the common carotid bifurcation. Proximal control is achieved by inflating the balloon. Distal control is then gained by temporary clipping just proximal of the origin of PcomA. 4 Retrograde suction decompression through the catheter partially collapses and softens the aneurysm. 1, 4, 6 - 8 Carotid occlusion was applied twice, 2:47 and 2:57 min. Intraoperative angiogram revealed the obliteration of the aneurysm and the patency of the carotid and ophthalmic artery. The patient recovered well, and visual deficit resolved and was neurologically intact. Patient consented for surgery. Illustrations in video reprinted with minimal modification from Surgical Neurology, vol 50, issue 6, Arnautović KI, Al-Mefty O, Angtuaco E, A combined microsurgical skull-base and endovascular approach to giant and large paraclinoid aneuroysms, 504–518, 4 Copyright 1998, with permission from Elsevier Science Inc.